2019
DOI: 10.19101/ijatee.2019.650010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a wireless sensor network based smart multiple ambient conditions sensing system for the rearing process of eri silkworm

Abstract: Assam has a strong contribution in the world silk production. Several rural families of this region are engaged in this activity. Socioeconomic development of this region is also dependent on these activities. This paper presents a wireless sensor network-based instrumentation to record the process conditions of the rearing process of eri silkworm, which canfurther help to optimize the rearing process. For this purpose, temperature, relative humidity, light intensity takes as major process parameters on which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It only serves as a learning material for compression and decompression techniques of Huffman Coding [14]. The use of Huffman Coding for data transmission proves its high efficiency in this study, however the project does not support real-time simultaneous data collection, which is not ideal for weather monitoring buoys [19].…”
Section: Consmentioning
confidence: 93%
See 2 more Smart Citations
“…It only serves as a learning material for compression and decompression techniques of Huffman Coding [14]. The use of Huffman Coding for data transmission proves its high efficiency in this study, however the project does not support real-time simultaneous data collection, which is not ideal for weather monitoring buoys [19].…”
Section: Consmentioning
confidence: 93%
“…The most significant parameters in WSN concerned for CH selection are energy, delay and distance [13]. Doloi et al [14] used CC2500 Radio Frequency (RF) modem as a transceiver module which is a straightforward communication at 2.4 GHz, and a short distance module which is not a problem for this study doesn't require long range. It also used star topology, and the difference is the data gathered is not sizable enough to cause slower transmission, thus doesn't require digital signal processing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakhale et al (2014) [14] study in India and Singh et al (2002) [21] reported longer larval duration of 29±3 days, which they attributed to differences in temperature and humidity, which could explain the results reported in the current study. The ideal temperature range for Eri worm rearing is between 20 o C and 35 o C and an increase in temperature beyond that causes less spinning and mortality in larvae (Doloi et al 2019) [3] the reason why Eri worms did not survive to 5 th instar, in L6 and L7 could be due to these conditions.…”
Section: Larval Duration and Survivalmentioning
confidence: 99%